Over-the-counter L-arginine supplements to improve human performance - Soderman, Robert (University of Wisconsin--Whitewater, 2013)
The purpose of this research was to evaluate the benefits to human performance of over-the-counter L-arginine supplements. 20 male and 15 female track and field athletes from a NCAA Division III university performed two exercise trials consisting of a thirty second standard Wingate Anaerobic Power Cycle Ergometer Test with a force setting based on 7.5% of body weight. 30 minutes prior to each exercise trial the subjects consumed 5,000 mg of GNC L-Arginine 5000® in eight ounces of water (L-arginine trial) or the equivalent volume of plain water (control trial). The 5,000 mg dosage was based upon the manufacturer's guidelines found on the supplements packaging. Peak power (W/kg) was higher during L-arginine trials compared to control trials, these differences were statistically significant for women (p=0.0435) and all subjects (combined, p=0.0303), and approached statistical significance for men (p=0.0811). Average power (W/kg) was higher during L-arginine trials compared to control trials, but these differences approached statistically significance only for women (p=0.0520). Based upon subject weight, men received an average of 57.7 mg of L-arginine per kilogram of body weight while women received an average of 79.9 mg of L-arginine per kilogram of body weight. 15 of 35 subjects (42.9%), including 9 of 20 men (45.0%) and 6 of 15 women (40.0%), reported feeling lightheaded, dizzy or nauseated following the L-arginine trials, while no subjects reported the "muscle pumps" or "excited" feeling advertised by the manufacturer following the L-arginine trials. The manufacturer's recommended dosage of L-arginine may be an effort to simplify the dosage and avoid calculations for the consumer, but also may be balancing increasing the incidence of feeling lightheaded, dizzy or nauseated against additional improvements in performance that might result from a larger dosage per kilogram. The manufacturer's recommended dosage of L-arginine improved peak performance, but did not improve average performance, during the thirty second standard Wingate Anaerobic Power Cycle Ergometer Test, especially in women who received a higher dosage of L-arginine per kilogram of body weight. The manufacturer's recommended dosage of L-arginine may improve performance in rapid explosive movements, but those improvements may not be sustained over longer periods of exercise.
File was last viewed in Adobe Acrobat Pro.
Keywords: Arginine--Physiological effect; Sports--Physiological aspects; Dietary supplements